Correlation between Caries Related Microorganisms in the Dental Plaque and Saliva with Dental Caries Level in the Upper and Lower Jaws in 5-9 Years Old Children in Baghdad City - Zainab Juma'a; Raghad Fadhil; Yasameen Abdul-Hussain (Journal of Baghdad College of Dentistry, 2016)
Background: The oral cavity is considered as a complex ecological niche, its complex microbial community is reflected to it. Streptococcus mutans has been implicated as one of the major etiological factor of dental caries. Tooth surfaces colonized with Streptococcus mutans are at a higher risk for developing caries, while lactobacilli are considered as the secondary invaders, not initiators of the carious lesion. The main purpose of this study was to correlate the dental caries (for primary and permanent teeth) in the upper jaw with the streptococcus mutans and lactobacilli count in the dental plaque and saliva, also to correlate the dental caries (for primary and permanent teeth) in the lower jaw with the streptococcus mutans and lactobacilli count in the saliva. Materials and methods: Forty seven children aged 5-9 years old were selected for this study. Dental caries recording was carried out by the dmfs index (decayed, missed, filled surfaces for primary teeth) to inspect the primary teeth and DMFS index (decayed, missed, filled surfaces for permanent teeth) to inspect the permanent teeth, by using the dental mirror and explorer. Collection of salivary samples was performed in the morning between (10-11) a.m. at least one hour after breakfast, then normal saline was added to have tenfold dilutions, for the purpose of full colony counting of the caries related microorganisms (streptococcus mutans and lactobacilli), then inoculation was done in the special selective media (for the streptococcus mutans is Mitis-Salivarius-Bacitracin agar, and for the lactobacilli is Rogosa agar). Counting of the colonies of the bacteria were estimated by the aid of dissection microscopeResults: The highest level of dmfs means was found in primary upper teeth, it was 17.6383 Â± 10.10 while for the permanent teeth the mean of DS and DMFS was highest in the lower teeth, it was 0.7391 Â± 1. Pearson correlation was used to show the correlation between the ds and dmfs of upper and lower primary teeth with the level of streptococcus mutans in saliva (sm. Sal) and lactobacillus in saliva ,there was a significant correlation between the ds and dmfs for upper primary teeth at level 0.01 (2-tailed), and there was negative correlation between dsl and level of streptococcus mutans in saliva (sm. Sal) also there was negative correlation between dmfs for upper and lower primary teeth with level of streptococcus mutans in saliva, also the correlation between lactobacillus level in plaque with streptococcus level in plaque was negative, while for upper permanent teeth the correlation was negative with both type of bacteria level in plaque with the DSU and DMFSUConclusion: The caries activity was more prominent in upper teeth than lower teeth, levels of streptococcus mutans were not associated with high caries activity, which emphasizes and consistent with the fact that the dental caries is a multifactorial disease, related to many factors.